2018
DOI: 10.13189/ujer.2018.061120
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interactive Whiteboard Applications Supported by Visual Materials on Middle School Students' Listening Comprehension and Persistence of Learning

Abstract: In this study, it was examined how interactive whiteboard applications supported by visual materials affected middle school students' listening comprehension and persistence of learning. The sample of the study consisted of the students in the 8/D (experimental group) and 8/H (control group) cohorts of the Osman Gazi Middle School located in Palandöken central district of Erzurum province during the spring semester of the 2017-2018 school year. The study was carried out as a pre-test post-test experimental des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In the literature review, Akar (2020) found that many studies provide positive conclusions about smart technologies' contribution to teaching and learning. However, Kirbas (2018) found the technology insufficient as many schools have challenges with adequate instructional hours. The study found significant academic achievement of students in the experimental group than in the control group (Kirbas, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature review, Akar (2020) found that many studies provide positive conclusions about smart technologies' contribution to teaching and learning. However, Kirbas (2018) found the technology insufficient as many schools have challenges with adequate instructional hours. The study found significant academic achievement of students in the experimental group than in the control group (Kirbas, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, Kirbas (2018) found the technology insufficient as many schools have challenges with adequate instructional hours. The study found significant academic achievement of students in the experimental group than in the control group (Kirbas, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It corresponds to Chang and Millett's (2014) study, which concluded that simultaneous listening-and-reading was proven more effective than only reading or listening. According to Kirbas (2018), learners can recall the materials more effectively when facilitated with written texts and pictures. Other studies also confirmed that reading a text simultaneously while listening to it being spoken helps give deeper comprehension and further understanding of vocabulary recognition (Gobel & Kano, 2014).…”
Section: I S T E N I N G W I T H O U T R E a D I N G T H E T R A N S C R I P T S W R I T I N G D O W N N E W V O C A B U L A R I E S S H mentioning
confidence: 99%